Linear and non-linear system theory - Thyagarajan, T.; Kalpana, D. (Boca Raton, FL : CRC Press, 2021)
Linear and Non-Linear System Theory focuses on the basics of linear and non-linear systems, optimal control and optimal estimation with an objective to understand the basics of state space approach linear and non-linear systems and its analysis thereof. Divided into eight chapters, materials cover an introduction to the advanced topics in the field of linear and non-linear systems, optimal control and estimation supported by mathematical tools, detailed case studies and numerical and exercise problems. This book is aimed at senior undergraduate and graduate students in electrical, instrumentation, electronics, chemical, control engineering and other allied branches of engineering. Features Covers both linear and non-linear system theory Explores state feedback control and state estimator concepts Discusses non-linear systems and phase plane analysis Includes non-linear system stability and bifurcation behaviour Elaborates optimal control and estimation
Determination of State Observer Gain Matrix (K(0)) -- 4 Non-Linear Systems and Phase Plane Analysis -- Characteristics of Non-Linear Systems -- Jump Resonance -- Types of Nonlinearities -- Saturation -- Deadzone -- Backlash -- Friction -- Describing Function Fundamentals -- Describing Function of Deadzone -- Describing Function of Saturation Nonlinearity -- Describing Function of Deadzone and Saturation -- Describing Function of On-Off Controller with a Deadzone -- Describing Function of Backlash Nonlinearity -- Describing Function of Relay with Deadzone and Hysteresis -- Phase Plane Analysis
OCLC-licensed vendor bibliographic record.
Keywords: Linear systems; Nonlinear systems; TECHNOLOGY / Electricity; TECHNOLOGY / Engineering / General